Digital Dementia Registry Bavaria - DigiDEM Bayern: Study protocol for a multicentre, prospective, longitudinal register study - Dietzel, Nikolas; Kürten, Lara; Karrer, Linda; Reichold, Michael; Köhler, Laura; Nagel, Andreas; Chmelirsch, Christina; Seebahn, Kathrin; Hladik, Markus; Meuer, Sebastian; Kirchner, Anna; Holm, Kristina; et al. (BMJ Open, 2021)
Introduction Dementia is one of the most relevant widespread diseases, with a prevalence of currently 50 million people with dementia worldwide. The care of people with dementia will be one of the major challenges for healthcare systems worldwide. Digitalisation offers new possibilities to improve both dementia healthcare and health outcomes research as a fundament for national healthcare planning. The a € Digital Dementia Registry Bavaria - digiDEM Bayern' aims to improve the understanding of the complexity and long-term progression of dementia and the current care situation in Bavaria. Moreover, by offering digital services, digiDEM will actively contribute to improving the care situation in Bavaria. Methods and analysis digiDEM will recruit people with dementia and their family caregivers in all administrative regions of Bavaria. All participants will undergo dementia screening prior to study inclusion in order to identify people with mild cognitive impairment and mild-to-moderate dementia. Participants will be followed up over a period of three years. Sociodemographic data, type of dementia, symptoms, diagnosis, cognitive trajectories, activities of daily living, behavioural and psychological symptoms, falls, resource utilisation, caregiver burden, quality of life, needs of people with dementia and their caregivers, mobility, use of media and sources of information will be assessed. The project will implement a digital web-based platform for data collection. Data will be collected by means of standardised online or face-to-face interviews. Ethics and dissemination The study obtained ethical approval from the Ethics Committee of the Medical Faculty of Friedrich-Alexander-University Erlangen-Nürnberg (FAU) (application number: 253_20 B). Findings will be used for evidence-based decision-making for health decision-makers in order to optimise dementia healthcare in the state of Bavaria. Specific analyses will be conducted for the participating research partners. Results of the study will be published in peer-reviewed journals.
CRIS-Team Scopus Importer:2021-02-26
Keywords: dementia; neurology; public health

Predictors of the one-year-change in depressiveness in informal caregivers of community-dwelling people with dementia - Kürten, Lara; Dietzel, Nikolas; Kolominsky-Rabas, Peter; Grässel, Elmar (BMC Psychiatry, 2021)
Background: The care of people with dementia is usually carried out by their family members, which can cause objective und subjective burden and raise their risk of depressiveness. Thus, the aim of this study is to identify predictors of the change in depressiveness of informal caregivers over 1 year in order to be able to derive hypotheses for interventions that promise success. Methods: The Bavarian Dementia Survey (BayDem) is a multi-center, longitudinal study conducted at three different sites in Bavaria, Germany. Participants were people with dementia and their informal caregivers. Data was collected at baseline and after 12 months by standardized face-to-face interviews in cooperation with local players. The informal caregivers’ depressiveness was assessed with the WHO-5. Data was also collected on the people with dementia’s cognition (MMSE), behavioral symptoms (NPI) and comorbidities (Charlson Comorbidity Index) as well as caregivers’ social inclusion (LSNS), time spent on care and care contribution (RUD). For statistical analysis, a multiple regression model was used. Results: The data of 166 people with dementia and their informal caregivers was analyzed. Of the latter, 46% were categorized as “likely depressed”. The change in depressiveness over a year was significantly predicted by baseline depressiveness as well as an increase in the time informal caregivers spent supervising the person with dementia. Conclusions: Informal caregivers of people with dementia are at high risk of depression. The time spent supervising the person with dementia has a significant impact on increasing depressiveness. This highlights the importance of support services to provide the informal caregiver with relief and possibly reduce depressiveness.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Dementia; Depressiveness; Informal caregivers; Longitudinal; Predictors; Supervision time; WHO-5

The Dementia Assessment of Service Needs (DEMAND): Development and Validation of a Standardized Needs Assessment Instrument - Dietzel, Nikolas; Grässel, Elmar; Kürten, Lara; Meuer, Sebastian; Klaas-Ickler, Dorothee; Hladik, Markus; Chmelirsch, Christina; Kolominsky-Rabas, Peter (Journal of Alzheimer's Disease, 2022)
BACKGROUND: Dementia is one of the main triggers for care dependency among older adults who are predominantly cared for at home by relatives. To provide support in the care situation, health systems need valid information about the central needs of the affected people. OBJECTIVE: The present study aimed to develop a research instrument to assess the most important needs of people with dementia and their family caregivers. METHODS: The development of the 'Dementia Assessment of Service Needs (DEMAND)' took place within the project 'Digital Dementia Registry Bavaria (digiDEM Bayern)'. A focus group and an online survey with dementia experts were conducted to identify the most relevant support services and to develop the design of the instrument. The questionnaire was deployed in the digiDEM baseline data collection. Participants were asked to evaluate the comprehensibility of the questionnaire. Readability was assessed using the Flesch reading ease score. RESULTS: Seventeen experts participated in the focus group and 59 people in the online survey. The final questionnaire included 13 support services. One hundred eighty-three participants (50 people with dementia and 133 family caregivers) completed the questionnaire at baseline. The mean comprehensibility score was 3.6 (SD = 2.3). The Flesch reading ease score result was 76. CONCLUSION: A research instrument could be developed, enabling people with dementia and family caregivers to directly express their individual needs for specific support services. Results show that the DEMAND is easy to understand and short in execution. Therefore, supply gaps can be identified and transformed into a specific health care plan.
CRIS-Team Scopus Importer:2022-10-21
Keywords: Demand; dementia; digiDEM; health services research; needs; resource use